(3beY GdfahS hQbjI GdeCjhSs - (3CHh HcQ Hf eMeO Hf YHO GdeDef Hf nMpQjR Hf eYnqdj GdMSjfj GdMUfj, Jbqj GdOjf,J (B829 (3g` s ((3Ydi Hf eMeO GdfGSN s)
(3ChdgG (B:s
(3hHYO aEf GdfGS cGfhG ai LGgdjI LgdkG hYejI YejkG MJi LGA GdMb hRgb GdHGWd Ef GdHGWd cGf RghbG bGd Gddg JYGdi (B: ( (3EfG CQSdfGc HGdMb HTjQG(B) s
(3BNQgG (B:s
(3bO WGd eG CcdhG jhekG heG TQHhG aCUHMhG HYO Pdc GdCcd bO CcdhG hfNJe GdcJGH Hbhd CHj GdOQOGA QVi Gddg Yfg deG ONd GdTGe bGd dG dge jG Cgd GdTGe GSeYhG bhd CN fGUM aCUHM Cedge ZQhQkG hLeYg HhQkG heSGcfge bHhQkG s
(3gPg gi GdfSNI GdKGdKI ef GdeNWhWGJ dgPG GdcJGH GdChdi ai HQdjf hGdKGfjI ai CcShaQOs
(3hgPg GdfSNI GdKGdKI cJHJ HYO GdeDda HCbd ef SJjf SfIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B74s
Keywords: (3GdJUha hGdBOGH GdTQYjIs